(3Jbjje GdBKGQ GdEbJUGOjI hGdELJeGYjI dbQhV HQfGeLj GdCSQ GdefJLI hUfGOjb GdGFJeGf GdefaPjgf ef hRGQI GdJfejI GdGLJeGYjI aj GdCQOf (B/s - (3TJjhj, ehSis ((3GdbGgQI(B: s (3ecJHI RgQGA GdTQb(B, s, 2001)
(3GdNUGFU GdEbJUGOjI hGdELJeGYjI ddebJQVjf(B- (3GdNUGFU GdYGeI ddeTGQjY , Jbjje GdebJQVjf dHYV GdbVGjG GdGSGSjI GdeJYdbI HYedjI GdEbJQGV, Jbjje GdBKGQ GdEbJUGOjI ddeTGQjY Ydi GdebJQVjf , GdGSQ GdefJLI hUfGOjb GdEFJeGf, GdYhGed GdeMOOI dESJeQGQjI hfLGM GdeTGQjY , GdfJGFL hGdJhUjGJs
Keywords: (3GdEbJUGOs; (3GdbQhVs